Sifat Mekanik dan Densitas Ikatan Silang Hidrogel berbasis Tapioka Nanopartikel - Puspita, Indah; Kurniati, Mersi (Jurusan Fisika, Universitas Bangka Belitung, 2022)
Tapioca is a natural polymer that is widely used as a raw material for hydrogels. In order to improve the mechanical properties of tapioca-based hydrogels, this research modified tapioca by acid hydrolysis method for 2 hours and 24 hours and by ethanol precipitation method. This modified tapioca was further treated with epichlorohydrin with various concentrations of 0, 5, 10, and 20% to produce a three-dimensional cross-linked structure. The results showed that the increasing of epichlorohydrin concentration led to an increasing in the mechanical properties of the hydrogels consisting of hardness, stress, modulus of elasticity, and cross-linked density. The hydrogel from tapioca hydrolyzed for 24 hours and 20% epichlorohydrin was the sample with the best mechanical properties with a hardness of 19.78 mJ, a stress of 78.65 kPa, a modulus of elasticity of 233.84 mJ, and a cross-linked density of 57.61 × 1024 m-3.